Pengaruh motivasi ekstrinsik dan pelatihan kerja terhadap kinerja karyawan dealer astra motor honda jepara - Laili Safitri; Kusni Ingsih; Nanda Adhi Purusa; Tito Aditya Perdana (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This study aims to analyze the influence of extrinsic motivation and job training on employee performance at the Astra Motor Honda Jepara Dealership, and to examine the role of job training as a mediating variable in the relationship between extrinsic motivation and employee performance. This study uses a quantitative approach supported by interviews with 58 employees. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4 software. The results showed that extrinsic motivation had a positive and significant effect on employee performance (β = 0.464; p < 0.001). Job training also had a positive and significant effect on employee performance (β = 0.521; p < 0.001). In addition, extrinsic motivation had a positive and significant effect on job training (β = 0.939; p < 0.001). The results of the mediation test showed that job training was able to significantly mediate the relationship between extrinsic motivation and employee performance. These findings indicate that a combination of an external incentive system and an effective and applicable job training program can optimally improve employee performance. This research provides theoretical contributions to the development of Self-Determination Theory in human resource management and offers practical implications for dealership management in developing competency development strategies and improving employee performance.